The sustainability through Mathematics: A Necessary Interdependency (International Journal of Food and Nutritional Sciences, 2022)
Guarantying a sustainable future for our children is truly the greatest challenge facing humanity and raises a profusion of scientific and mathematical challenges. In the language of the Brundtland Report, World Commission on Environment and Development, 1987, it means leaving for future generations the same options we have for how we want to live our lives. However, operational that concept is easier said than doneHere, Mathematical modelling is considered as an indispensable tool for sustainable development. Sustainable development is to balance our economic, environmental and social needs allowing prosperity for now and future generations. Mathematical Science plays as tackle the challenges facing our planet. Mathematical modelling plays useful roles towards sustainable development in arriving the understanding, prediction and control of development process. Mathematical modelling can be a powerful tool for understanding and observed phenomena which cannot be understood by verbal reasoning alone. It is conclude that for sustainable development, it is necessary to build mathematical model.